Analisis Bauran Pemasaran Dan Pengaruh Citra ProdukShuttlecock Terhadap Keputusan Pembelian YangBerdampak Pada Kepuasan Konsumen(Di Perusahaan Shuttlecock "LIYA") - Gunawan, Achmad, Ahmad Kholid Al Ghofari, ST. MT (2017)
Creation of an impression to a brand become one of the tools to attract consumers, so that consumers are more loyal to a brand and make consumers remember the brand. This study aims to analyze a variable marketing mix and brand image to a purchasing decision that impact on customer satisfaction. The samples used for this study as many as 100 of those consumers who buy products shuttlecock LIYA. Sample was taken by purposive sampling or data collection with particular consideration the samples in this study are some consumers who purchase and trust products shuttlecock LIYA more than once. Testing study using multiple linear regression. For the results of this study can be concluded that of the marketing mix had a positive influence on purchase decisions (2,445) with a significance value of 0.016, so that the brand image does not have a positive influence on purchasing decisions and consumer satisfaction (-0.211) with a significance value of 0,833 and a decision purchases positive effect on customer satisfaction (.224) with a significance value of 0.027.